The Effect Of Comic Books To Improve Reading Comprehension Ability At Grade VIII At SMP N 12 Pematangsiantar - Indra Jayanti Damanik; Grace Sari Harianja (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2022)
This study was aimed at investigating whether“Does comic books effect to improve student’s reading comprehension skill of narrative text at grade VIII SMP N 12 Pematangsiantar?”This research was a quantitative approach. For the data collection, there werePre-test and Post-test. The population of this study was the students the Eighth grade of SMP N 12 Pematangsiantar has 5 classes which of 184 studentswith a sample50 students. The data analysis started fromscoring composition and finding average of the score.Based on the data analysis the researcher finding also provedthe Score Pre-test of Control is 1308 and for average of control class is 52, 32. The Score Post-test of Control Classis 1484 and for average of control class is 59, 36. The Score Pre-test of Experimental Classis 1448 and for average of control class is 57, 92.The Score Post-test of Experimental Class is2060and for average of control class is 82,4